Cryptococcosis outbreak in psittacine birds in Brazil - Raso, T. F. [UNESP]; Werther, Karin [UNESP]; Miranda, E. T. [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Oxford University Press (OUP), 2004)
An outbreak of cryptococcosis occurred in a breeding aviary in São Paulo, Brazil. Seven psittacine birds (of species Charmosyna papou, Lorius lory, Trichoglossus goldiei, Psittacula krameri and Psittacus erithacus) died of disseminated cryptococcosis. Incoordination, progressive paralysis and difficulty in flying were seen in five birds, whereas superficial lesions coincident with respiratory alterations were seen in two birds. Encapsulated yeasts suggestive of Cryptococcus sp. were seen in faecal smears stained with India ink in two cases. Histological examination of the birds showed cryptococcal cells in various tissues, including the beak, choana, sinus, lungs, air sacs, heart, liver, spleen, kidneys, intestines and central nervous system. High titres of cryptococcal antigen were observed in the serum of an affected bird. In this case, titres increased during treatment and the bird eventually died. Yeasts were isolated from the nasal mass, faeces and liver of one bird. Cryptococcus neoformans var. gattii serovar B was identified based on biochemical, physiological and serological tests. These strains were resistant (minimum inhibitory concentration 64 μ g/ml) to fluconazole. This is the first report of C. neoformans var. gattii occurring in psittacine birds in Brazil. © 2004 ISHAM.
Keywords: Avian; Brazil; Cryptococcosis; Cryptococcus neoformans var. gattii; Psittacine birds; fluconazole; fungus antigen; animal cell; animal tissue; antibiotic resistance; beak; central nervous system; coordination; cryptococcosis; Cryptococcus neoformans; epidemic; feces analysis; female; flying; fungal cell; fungal strain; fungus isolation; heart; histopathology; intestine; kidney; liver; lung; male; minimum inhibitory concentration; nonhuman; paralysis; psittacine; respiratory tract disease; spleen; yeast; Animals; Bird Diseases; Disease Outbreaks; Female; Male; Psittaciformes; Aves; Charmosyna; Charmosyna papou; Cryptococcus bacillisporus; Cryptococcus sp.; Erithacus; Filobasidiella neoformans; Lorius; Lorius lory; Psittacula; Psittacula krameri; Psittacus erithacus; Trichoglossus